Effect of Yoga and Walking on Systolic Blood Pressure and Physical Fitness in Older People with Hypertension - Ely Tri Susiani; Yulia Lanti Retno Dewi; Siti Khoiriyah; Dhoni Akbar Ghozali; Adi Prayitno (Journal of Health Promotion and Behavior, 2026)
Background: Hypertension in the elderly is one of the most common health problems and is at risk of causing cardiovascular complications. Physical activities such as yoga and walking are seen as effective non-pharmacological interventions in helping control blood pressure, improving physical fitness, and providing a positive impact on the quality of elderly health services. This study aims to analyze the effect of yoga and walking on systolic blood pressure and physical fitness in older people with hypertension. Subjects and Method: This was an experimental study. The independent variable was yoga and walking program. The dependent variables were systolic blood pressure and physical fitness. The effect of yoga and walking interventions on systolic blood pressure and physical fitness was analyzed using Freadman test. Results: The results showed that yoga and walking had a significant effect on reducing systolic blood pressure in the elderly with (Sig. 0.001 <0.05). Spearman’s rho analysis results indicate that behavioral activity is significantly associated with all variables, as the p-value is < 0.001. The strongest association was found with pre-test systolic blood pressure (r = 0.78). Meanwhile, post-test physical fitness showed an r-value of 0.67, pre-test physical fitness r = 0.54, and systolic blood pressure r = 0.47. Conclusion: There is a significant difference in the effect of behavioral activity on systolic blood pressure and physical fitness in elderly people with hypertension, based on the Friedman test. Behavioral activity has been shown to contribute to lowering systolic blood pressure and improving physical fitness; there is a strong relationship between behavioral activity on systolic blood pressure and physical fitness based on the Spearman's rho correlation test.